ABoT 2.247, KBo. 57.180 und das Lied der Freilassung - Görke, Susanne 1974-; Lorenz, Jürgen (2024)
This article discusses two fragments written down during Hittite Empire times that have been attributed to the Hurrian-Hittite bilingual Song of Release (CTH 789) found at the Hittite capital Ḫattuša. The authors argue that ABoT 2.247 is a cadaster text, and that the classification of KBo. 57.180 as part of the Song of Release remains doubtful. Therefore, the transmission of the Hurrian Song of Release is limited to the era preceding the Hittite Empire, with all of its manuscripts exhibiting the Middle Script. It thus presents a rare example of Hittite text ensembles without any New Script copy. The article outlines previous thinking about this phenomenon and re-evaluates it by adding evidence of comparable text corpora and aspects of Hittite scholarship.
Keywords: Hittite scholarship; Hittite-Hurrian bilingue; Middle Hittite manuscripts; Song of Release; Temple XV and XVI; epic of Gilgameš; Tradition